Differentiation and on axon-guidance chip culture of human pluripotent stem cell-derived peripheral cholinergic neurons for airway neurobiology studies - Goldsteen, P. A.; Sabogal Guaqueta, A. M.; Mulder, P. P. M. F. A.; Bos, I. S. T.; Eggens, M.; Van der Koog, L.; Soeiro, J. T.; Halayko, A. J.; Mathwig, K.; Kistemaker, L. E. M.; Verpoorte, E. M. J.; Dolga, A. M.; et al. (Frontiers in Pharmacology, 2022)
Airway cholinergic nerves play a key role in airway physiology and disease. In asthma and other diseases of the respiratory tract, airway cholinergic neurons undergo plasticity and contribute to airway hyperresponsiveness and mucus secretion. We currently lack human in vitro models for airway cholinergic neurons. Here, we aimed to develop a human in vitro model for peripheral cholinergic neurons using human pluripotent stem cell (hPSC) technology. hPSCs were differentiated towards vagal neural crest precursors and subsequently directed towards functional airway cholinergic neurons using the neurotrophin brain-derived neurotrophic factor (BDNF). Cholinergic neurons were characterized by ChAT and VAChT expression, and responded to chemical stimulation with changes in Ca2+ mobilization. To culture these cells, allowing axonal separation from the neuronal cell bodies, a two-compartment PDMS microfluidic chip was subsequently fabricated . The two compartments were connected via microchannels to enable axonal outgrowth. On-chip cell culture did not compromise phenotypical characteristics of the cells compared to standard culture plates. When the hPSC-derived peripheral cholinergic neurons were cultured in the chip, axonal outgrowth was visible, while the somal bodies of the neurons were confined to their compartment. Neurons formed contacts with airway smooth muscle cells cultured in the axonal compartment. The microfluidic chip developed in this study represents a human in vitro platform to model neuro-effector interactions in the airways that may be used for mechanistic studies into neuroplasticity in asthma and other lung diseases.